The Effectiveness of Hybrid Learning Module on Basic Structure Course In IKIP Budi Utomo Malang - Indrawati Pusparini; Endang Setyo Astuti (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2019)
This article is an investigation into the effectiveness of hybrid learning module on basic structure in students university in Ikip Budi Utomo . This concepts related to hybrid learning and conventional classroom. There were 90 students who participated in this research . The study revealed that students prefer hybrid learning on basic structure to conventional classroom, paper and pencil . As the first, they seemed like to take English lessons in conventional form, paper and pencil, rather than in hybrid leaning form, because they used to study in conventional method. When they submitted English assignments online or personally, their opinions were changed. They finally trusted to hybid learning method. This method of the research use quantitative method.The research found that significantly different capability in basic structure comprehension. The obtained t-test value for hybrid learning module on basic structure was 7.85 while the critical value of p< .05 level of significance of one-tailed test was 1.671 (d.f.= 60 ). From the t-test computation, it can be concluded that the students taught by hybrid learning module had better capability than those the students taught in conventional, paper and pencil . In conclution, learning basic structure based on hybrid learning module is better than conventional method , paper and pencil. Additionally, some recommendations for future work in this field were made.